1967
DOI: 10.1139/p67-309
|View full text |Cite
|
Sign up to set email alerts
|

Transport Properties of Pure Metals at High Temperatures: I. Copper

Abstract: This paper is the hrst of a series reporting our investigations into the hightemperature properties of the monovalent metals. I t contains a description of the nlethods used in these investigations, and the results of measurements of the transport properties of pure copper, over the temperature range 300-1 250 'I<. These results are compared \\.it11 solue previously published work, and also with standard theoretical esprcssions applicable to the monovalent metals.'Issued as N.R.C. No. 9'760. *The non~enclature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

1978
1978
1988
1988

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…The values calculated from eqs. (12) and (35) are in good agreement with these measurements at those temperatures for which It was possible to calculate the lattice component. The investigation by Fletcher and Greig 1841 of the thermal conductivity of palladiumsilver alloys revealed that the strong electron-phonon interaction in palladium-rich alloys suppresses the low temperature lattice thermal conductivity, causing its maximum to occur at much higher temperatures than in silver-rich alloys.…”
Section: Zr'supporting
confidence: 79%
See 4 more Smart Citations
“…The values calculated from eqs. (12) and (35) are in good agreement with these measurements at those temperatures for which It was possible to calculate the lattice component. The investigation by Fletcher and Greig 1841 of the thermal conductivity of palladiumsilver alloys revealed that the strong electron-phonon interaction in palladium-rich alloys suppresses the low temperature lattice thermal conductivity, causing its maximum to occur at much higher temperatures than in silver-rich alloys.…”
Section: Zr'supporting
confidence: 79%
“…Such a deviation has been observed in Cu [12,13]. In transition metals normal electronelectron interactions between s and d band electrons contribute to the electrical resistivity as well as to the thermal resistivity; these processes are very strong [14,151 and are generally thought to be responsible for the T2 temperature dependence of the electrical resistivity observed in these metals at low temperatures.…”
Section: Electronic Thermal Conductivitymentioning
confidence: 79%
See 3 more Smart Citations